2016
DOI: 10.3389/fphys.2016.00606
|View full text |Cite
|
Sign up to set email alerts
|

Host-Microbiome Interaction and Cancer: Potential Application in Precision Medicine

Abstract: It has been experimentally shown that host-microbial interaction plays a major role in shaping the wellness or disease of the human body. Microorganisms coexisting in human tissues provide a variety of benefits that contribute to proper functional activity in the host through the modulation of fundamental processes such as signal transduction, immunity and metabolism. The unbalance of this microbial profile, or dysbiosis, has been correlated with the genesis and evolution of complex diseases such as cancer. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 242 publications
(280 reference statements)
0
24
0
Order By: Relevance
“…bile acids, where certain substances can only be formed via the interactions of human and bacterial genomes. [13,15,16] Studies from multiple groups have shown the microbiome has a role in many diseases including gastrointestinal disorders, [17,18] cancers and efficacy of cancer treatments, [19] metabolic syndrome and obesity[20] and a range of neuropathologies including Alzheimer's disease and autism. [21,22] The microbe-host connections in all these conditions are mediated via complex metabolic and immunological signalling mechanisms that are still poorly understood.…”
Section: Metabolite Originsmentioning
confidence: 99%
“…bile acids, where certain substances can only be formed via the interactions of human and bacterial genomes. [13,15,16] Studies from multiple groups have shown the microbiome has a role in many diseases including gastrointestinal disorders, [17,18] cancers and efficacy of cancer treatments, [19] metabolic syndrome and obesity[20] and a range of neuropathologies including Alzheimer's disease and autism. [21,22] The microbe-host connections in all these conditions are mediated via complex metabolic and immunological signalling mechanisms that are still poorly understood.…”
Section: Metabolite Originsmentioning
confidence: 99%
“…Understanding the host-microbiome interactions is central to understanding a number of diseases that are a consequence of dysbiosis including cancer [20,27]. Microbiome sequencing has facilitated significant research in this area and has enabled development of microbiota based therapy [270]. Metagenome sequencing has made possible rapid detection of pathogens and understanding of the evolution of hypervirulent and multidrug-resistant strains.…”
Section: Precision Metagenomics and Meta-metabolomics In Precision Mementioning
confidence: 99%
“…The launch of the integrative Human Microbiome Project (iHMP) is a leveraging step toward that direction ( 77 ). As host–microbiome interactions include exchange of different small molecules, specifically metabolites and signaling molecules, metabolomics data appear as most informative ( 78 ). Databases are launched to share information on gut microbes paired with genome sequences and longitudinal multi-omics data ( 79 ).…”
Section: Ai and Secondary Omics Datamentioning
confidence: 99%